A diagnostic dilemma of progressive, unilateral mandibular swelling: A mirage unveiled - Anwesha Bhattacharjee; S Bhuvaneshwari; Saba Khan; Bipin A Bulgannawar (Wolters Kluwer Medknow Publications, 2019)
Ossifying fibroma is a rareentity among the other type of fibro-osseous lesions. It is a non-odontogenic, benign tumor of the jaw, which arises from the multipotential cells of the periodontal ligament. Previously in 1992, WHO classified this type of lesion into ossifying fibroma and cemento-ossifying fibroma. Now the term- "cemento-ossifying fibroma" is replaced with "ossifying fibroma" in recent WHO classification (2005). These tumors are slow growing, painless and occur more commonly in the mandible and in the third and fourth decades of life with slight female predilection. Hereby, in this article, an unusual case of central ossifying fibroma in an 80-year-old female patient with expansile swelling of the right side of mandible since 2 months is repotred. The diagnosis was further confirmed by Cone beam computed tomography (CBCT) and histopathological evaluation. The main objective of this article is to enlighten about the diagnostic dilemma of mandibular swellings and atypical clinical behavior of central ossifying fibroma.